Pengaruh Current Ratio Dan Net Profit Margin Terhadap Harga Saham Dengan Earning Per Share Dan Dividend Per Share Sebagai Variabel Mediasi Pada Perusahaan LQ. 45 Di Bursa Efek Indonesia Tahun 2019-2022 - Bella Suci Maylianawati; Sri Harjanto; Dwi Rahayu (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to analyze the influence of the Current Ratio and Net Profit Margin on share prices with Earning Per Share and Dividend Per Share as mediating variables in LQ45 companies on the Indonesia Stock Exchange in 2019-2012. The sample taken was based on a saturation number of 180 companies. The data collection method used in this research is documentation, and the analysis technique uses regression analysis (path analysis) and the sobel test. The research results show that the Current Ratio has no effect on Earning Per Share and Net Profit Margin has a positive effect on Earning Per Share. Current Ratio and Net Profit Margin have no effect on Dividend Per Share. Current Ratio, Net Profit Margin, Earning Per Share, and Dividend Per Share have no effect on share prices. Earning Per Share is unable to mediate the Current Ratio of Share Prices. Earning Per Share is able to mediate Net Profit Margin on Share Prices. Dividend Per Share is not able to mediate the Current Ratio and Net Profit Margin on Share Prices.